The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1365-2885.2011.01338.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of enrofloxacin and its active metabolite, using anin vivoultrafiltration sampling technique after the injection of enrofloxacin to pigs

Abstract: The objective of this study was to determine the pharmacokinetics (PK) of enrofloxacin in pigs and compare to the tissue interstitial fluid (ISF). Six healthy, young pigs were administered 7.5 mg/kg enrofloxacin subcutaneously (SC). Blood and ISF samples were collected from preplaced intravenous catheters and ultrafiltration sampling probes placed in three different tissue sites (intramuscular, subcutaneous, and intrapleural). Enrofloxacin concentrations were measured using high-pressure liquid chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 27 publications
4
52
0
Order By: Relevance
“…Our results were in agreement with previous studies which indicated that ciprofloxacin levels (an active metabolite of enrofloxacin) were too low in the plasma of pigs and enrofloxacin could be served as the marker for PK calculation (10,11). Based on the concentration-time curve of plasma enrofloxacin, a series of pharmacokinetic parameters for the 12 piglets were derived from a one-compartment model (see Table 1).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Our results were in agreement with previous studies which indicated that ciprofloxacin levels (an active metabolite of enrofloxacin) were too low in the plasma of pigs and enrofloxacin could be served as the marker for PK calculation (10,11). Based on the concentration-time curve of plasma enrofloxacin, a series of pharmacokinetic parameters for the 12 piglets were derived from a one-compartment model (see Table 1).…”
supporting
confidence: 79%
“…The lower PK-PD breakpoint in our study may be due to the lower dose of drug administration to pigs, because previous studies concluded that the dose of drug administration may affect the PK-PD breakpoint (11,13,14). The PK-PD cutoff developed in our study should be more conservative, because it was generated based on the lowest approved dosage regimen for enrofloxacin (15).…”
mentioning
confidence: 60%
“…Therefore, it is necessary to determine the active concentration of free antimicrobial drugs at the target site using PK-PD modeling to achieve a rational dosage regimen. Previous studies have reported the application of an ultrafiltration sampling technique for isolating the free (unbound) drug in the gastrointestinal tract of calves, and in the ISF of different tissues (e.g., intramuscular, subcutaneous, and intrapleural tissues) of calves, sheep, and pigs 27, 28, 30, 31 .…”
Section: Introductionmentioning
confidence: 99%
“…In the most cases, the half-life of antibiotic residues is very high, and they can contaminate both terrestrial and aquatic environments. In un-developed countries, high level of antibiotic residues are found in different types of meat, up to 10 mg kg −1 [1,2].…”
Section: Introductionmentioning
confidence: 99%